The lord of the rings - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. (Boston : Houghton Mifflin, 1994)
J. R. R. Tolkien's classic novel in which the hobbit Frodo and the Fellowship of the Ring undertake a great quest--to journey across Middle-earth and cast the One Ring, filled with the power of the Dark Lord Sauron, into the Cracks of Doom.
The fellowship of the ring -- The two towers -- The return of the king.
Includes indexes.
Young Adult
Young Adult
Keywords: Baggins, Frodo (Fictitious character) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Baggins, Frodo (Fictional character) -- Fiction; Fantasy fiction; Middle Earth (Imaginary place) -- Fiction